A MATHEMATICAL MODEL OF AN ABSORPTION REFRIGERATION SYSTEM FOR A REFRIGERATED STORAGE FOR FISHING BOATS - Gonçalves, R. S. R.; Jacob-Furlan, B.; Kollross, E. C.; Berndsen, J. C.; Silveira da Silva, P. A.; Martins, L. S.; Mariano, A. B.; Ordonez, J. C. (Revista de Engenharia Térmica, 2022)
The objective of this paper is to determine if it is possible to refrigerate an area by means of a heat source. Theory determines that an absorption refrigerator can work as a possible solution through a refrigeration fluid. According to it, the system works by the evaporation or condensation of the working fluid. The traditional process consists of using engine fuel to run an electric compressor and by its means achieve refrigeration. That process has its toll on fuel economy and engine efficiency and the refrigeration fluid damages the ozone layer or is based on the transportation of ice previously bought on shore. The technological improvement will be equipped on fishing boats, in order to make the trip last longer due to the possibility of not needing to buy and transport ice and for the purpose of lowering the fishing industry cost. Absorption refrigeration can augment engine efficiency by using heat energy that is normally wasted and the system could reach temperatures of freezing water, meaning that it could be possible to follow Brazilian and international standards. The methodology of this work consists of an energy analysis of an absorption refrigerator, which is the determination of the heat transfer equations on the ammonia evaporator, condenser and exhaust/ammonia. Furthermore, it should be analyzed if it’s possible to determine to which working parameters the system will have an optimum operation. From the mathematical analysis, the system shows that with the equations it is possible to operate an absorption refrigeration based on the exhaust gases of fishing boats. Furthermore, the process can be operated on a wide range of temperatures, being possible to determine according to a few dimensionless parameters to which temperature levels the process of refrigeration shows the best removal of heat.